2016
DOI: 10.1016/j.psyneuen.2015.12.011
|View full text |Cite|
|
Sign up to set email alerts
|

Hypothalamic orexin’s role in exacerbated cutaneous vasodilation responses to an anxiogenic stimulus in a surgical menopause model

Abstract: Distressing symptoms such as hot flashes and sleep disturbances affect over 70% of women approaching menopause for an average of 4–7 years, and recent large cohort studies have shown that anxiety and stress are strongly associated with more severe and persistent hot flashes and can induce hot flashes. Although high estrogen doses alleviate symptoms, extended use increases health risks, and current non-hormonal therapies are marginally better than placebo. The lack of effective non-hormonal treatments is largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…One may thus speculate that the higher levels of hypocretin-1-ir in female patients may enhance depressive symptoms. It should be noted that since all the female subjects studied in our study were in their postmenopausal stage, one would not expect to see the hot flash-related hypocretin changes reported earlier ( Federici et al, 2016 ).…”
Section: Discussionmentioning
confidence: 70%
“…One may thus speculate that the higher levels of hypocretin-1-ir in female patients may enhance depressive symptoms. It should be noted that since all the female subjects studied in our study were in their postmenopausal stage, one would not expect to see the hot flash-related hypocretin changes reported earlier ( Federici et al, 2016 ).…”
Section: Discussionmentioning
confidence: 70%
“…Yohimbine, an α 2 -adrenoceptor antagonist, is known to cause hot flashes through the reduction of the thermoneutral zone, which affects temperature homeostasis [30,31]. FG-7142, calcitonin gene-related peptide, and neurokinin B have also been used to trigger hot flashes [32,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…A weakness of the present rodent studies was that only CO 2 was used as a stressor. However, we recently demonstrated that the GABAergic compound FG-7142 (a partial inverse benzodiazepine receptor agonist) which causes anxiety and flushing clinically (39) elicited rapid hot flash-associated increases in TST in OVEX rats but not sham control rats (40). Other studies have previously documented that stress-related stimuli, including mental arithmetic or emotionally salient films, can increase the rate of objective and subjective hot flashes (12) and self-reports implicate stressful stimuli (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Noradrenergic and serotonergic neurons in the midbrain pons and medulla also exhibit hypercapnic responsivity (28). Hypothalamic and brainstem sites including serotonergic nuclei (dorsal raphe and raphe pallidus) and noradrenergic nuclei (locus ceruleus) were found to significantly increase in response to FG-7142 hot flash provocation as well (40). These latter sites may be especially relevant to hot flashes in women because both the noradrenergic and serotonergic systems are treatments for hot flashes with selective serotonin and/or norepinephrine reuptake inhibitors (56, 57).…”
Section: Discussionmentioning
confidence: 99%